Pengkaryaan tari kreasi di SMP Negeri 3 Bissapu Kabupaten Bantaeng - Syakhruni, Syakhruni; Prusdianto, Prusdianto (DEDIKASI, 2020)
Dance as a form of art is an expression of human feelings expressed by body movements that have undergone processing, sterilization or distortion, which manifests into a natural aesthetic expression. Dance in the world of education, has a positive impact, not only for the preservation of dance, but also for the benefit of education itself. The age of junior high school students ranges from 13 to 15 years and belongs to the early adolescence group, where the transition from childhood to adulthood experiences development of all aspects or functions to enter adulthood. As a successor to the nation, if it is not directed to something positive, it could be that junior high school students will experience the tendency of negative traits as described previously. For this reason, a positive media is needed to build the positive character of middle school students who experience age transition. One of them is dance with its learning can be used as a means of expression, imagination and creativity to foster a rational and emotional balance, intellectual and aesthetic awareness. On the basis of these problems, a community activity program was made "Creative Work Creation PKM in Junior High School 3 Bissapu Bantaeng Regency". The results of these activities produce; (1) Creative Dance adds insight into students' skills in dance, (2) Through this activity students are familiar with dance and know the process of its creation, (3) The creation of creative dance performances based on the movement of the tradition of South Sulawesi.